A shot in the dark a creative DIY guide to digital video lighting on (almost) no budget - Holben, Jay (Course Technology PTR, 2012)
This book will show do-it-yourselfers how to create their own equipment and how best to use it. The first part of the book teaches about the basics--the fundamentals of light, color, exposure, and electricity--that are the building blocks of lighting. With that foundation, the book will introduce tips, techniques, and hands-on projects that instruct on how to create lighting tools from inexpensive, readily available resources. --from publisher description